Disappearance of an anticoagulation–resistant left atrial appendage thrombus after administration of low–dose pimobendan. Issue 4 (April 2020) - Sekihara, Takayuki; Sonoura, Takuryu; Nakamura, Yuka; Sunayama, Isamu; Morishita, Yu; Ishimi, Masashi; Yamato, Masashi; Yoshimura, Takahiro; Yasuoka, Yoshinori
Abstract: Anticoagulation therapy is essential for preventing thrombus formation in the left atrial appendage (LAA) and subsequent ischemic strokes in patients with atrial fibrillation (AF). The complete disappearance of any existing LAA thrombi is crucial before AF ablation. Currently, warfarin and direct oral anticoagulants are widely used for this purpose. However, treatment strategies for anticoagulation-resistant LAA thrombi are not well established. Here, we present a case of an 85-year-old male who was scheduled to undergo AF ablation. He developed an LAA thrombus that was resistant to 300 mg/day of dabigatran. Low-dose pimobendan was prescribed in addition to dabigatran; three months later, the thrombus was dissolved successfully. This case demonstrates the potential efficacy of a low-dose oral inotrope for treating an anticoagulation-resistant LAA thrombus. <Learning objective: Treatment strategies for anticoagulation-resistant left atrial appendage thrombi are not well established. This case demonstrates that a low-dose oral inotrope, such as pimobendan, is capable of dissolving such thrombi and is a potentially useful treatment modality.>